(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper investigates the possibility of passive athermalization of objectives for the long-wave infrared (LWIR) region of the spectrum. The main scientific problem is the difficulty in designing an athermalized objectives without the use of aspherical and diffractive surfaces and with the availability of a limited number of optical materials. A design methodology is applied, the focus of which is the use of materials with a negative thermal coefficient of refractive index and with specific values ​​of the refractive index and Abbe number. The results obtained show that the designed objectives are thermally stable in a wide temperature range and have the ability to work with medium-format FPA microbolometric arrays.